Pelatihan Teknik Visualsasi Untuk Menurunkan Stres Pada Pasien Diabetes Mellitus di Puskesmas Sukawati I Kabupaten Gianyar Tahun 2019 - I Nengah sumirta; i wayan candra; IGA Harini (Poltekkes Kemenkes Denpasar, 2020)
Degenerative diseases especially diabetes mellitus in indonesia has increased in line with the progress work in social economic and the changing lifestyle .International diabetic federation ( idf ) reckon incidence diabetes mellitus in the world 2012 as many as 371 million people , 2013 increased to 382 million people and diperirakan in the 2035 increased to 592 million people . In indonesia, according to the basic health research ( riskesdas ) years 2013 mentioned an increasing prevalence of diabetes mellitus based on the doctor diagnosis in at age ≥15 year in 2013 as much as 1,5 % and in 2018 2,00 %. as much as. This community service aims to reduce the level of stress in patients with Diabetes Mellitus. Using training methods, conduct stress level measurements before and after training, with a total target of 20 people. Data analysis using Paired Sample T-Test. The results show there is the influence of training visualize on the level of stress patients diabetes mellitus with p value much as 0.021 ( lt; 0.05 ) .Suggested in research locations to consider the use of visualize as one of the act of to reduce the level of stress patients diabetes mellitus and to respondents to conduct visualize continuously in any given period of time .Key Words: Diabetes Mellitus, Stress, Visualisasi